A2.24 IL23/TH17-mediated Regulation of Antibody Glycosylation Controls Autoimmune-Induced Arthritis. (25th February 2013) - Pfeifle, René; Magorivska, Iryna; Scherer, Ulrich; Harre, Ulrike; Rothe, Tobias; Böhm, Sybille; Herrmann, Martin; Blüml, Stephan; Nimmerjahn, Falk; Schett, Georg; Krönke, Gerhard
Abstract : Background and Objectives: Both rheumatoid arthritis (RA) and the murine models of collagen-induced arthritis (CIA) and of K/BxN arthritis are characterised by an initial break in self-tolerance, the appearance of specific autoantibodies and an autoantibody-mediated effector phase resulting in chronic inflammation and joint destruction. The IL23-dependent Th17 T-cell response has been identified as a major driving force during the pathogenesis of these disorders. The exact contribution of the IL23/Th17 axis to autoimmune-triggered inflammation, however, has remained incompletely understood. In this study, we aimed to further elucidate the role of IL23 and Th17 T-cells during murine autoimmune arthritis. Materials and Methods: To study and dissect the contribution of Th17 T cells to the initiation and effector phase of autoimmune arthritis, we performed the CIA as well as the K/BxN serum transfer model of arthritis in both wild-type (WT) mice and in mice lacking the IL23-specific subunit p19. Subsequently we determined the clinical course of disease as well as the serum levels, the avidity and the glycosylation pattern of antibodies in the sera of the respective mice. Results: While IL23 -/- mice, which lack functional Th17 T-cells, developed a full-blown arthritis after passive transfer of autoantibodies in the K/BxN model, these mice were resistant to collagen-induced arthritis. These data indicated that the IL-23/Th17 axis is dispensable during the autoantibody-mediated effector phase of arthritis, whereas it is crucially involved in mounting an autoimmune response during CIA. Despite being protected from CIA, IL23 -/- mice displayed regular levels of anti-collagen antibodies, which also showed a regular avidity. Likewise, we observed no difference in the IgG subclasses between the two genotypes. Analysis of the glycosylation pattern of antibodies in the sera of WT and IL23 -/- mice, however, revealed major differences in the content of sialic-acid and fucose residues at the Fc part of the IgGs resulting in an anti-inflammatory IgG profile in the sera of IL23 -/- mice. The changes in the IgG glycosylation, in turn, correlated with changes in the expression pattern of glycosyltransferases in plasmablasts and plasmacells of WT and IL23-deficient mice. Conclusions: Together, these data show that the IL23/Th17 axis controls the degree of antibody glycosylation and, in turn, indicate that this regulation of the glycosylation of autoantibodies is a critical step in the pathogenesis of Th17-mediated autoimmune diseases such as RA.